MoS2 incorporated hybrid hole transport layer for high performance and stable perovskite solar cells - Wang, D.; Elumalai, Naveen Kumar; Mahmud, M.; Yi, H.; Upama, M.; Lee Chin, R.; Conibeer, G.; Xu, C.; Haque, F.; Duan, L.; Uddin, A. (ELSEVIER SCIENCE SA, PO BOX 564, 1001 LAUSANNE, SWITZERLAND, 2018)
Two dimensional (2D) Transition Metal dichalcogenides have gained immense research attention in the recent years due to their superior opto-electronic properties and promising prospects in photonics and photovoltaic technologies. In this work, 2D Molybdenum disulphide (MoS2) nanoflakes were incorporated as hole transport layers (HTLs) in inverted (p-i-n) perovskite solar cells (PSCs). MoS2 nanoflakes were blended within the PEDOT:PSS layer together forming a hybrid HTL layer. The modified devices exhibited significant improvement in power conversion efficiency (PCE) and stability simultaneously. Compared to the control device, the efficiency enhancement of MoS2 incorporated devices was around 18.5%. The MoS2 nanoflake has improved the efficient charge extraction across the HTL layer reducing recombination at the interfaces, with a significantly lower electrode polarization and hysteresis. Impedance Spectroscopy (IS) analysis revealed that the MoS2 blended PEDOT:PSS HTL increased the recombination resistance by 50%. The modified HTL based devices also exhibited high device stability retaining more than 95% of the initial PCE even after 4 weeks.